A synopsis of the genus Stryphnodendron (Fabaceae, Caesalpinioideae, mimosoid clade) - Scalon, Viviane Renata; de Paula-Souza, Juliana; de Lima, Alexandre Gibau; Castro Souza, Vinicius (Phytotaxa, 2022)
Stryphnodendron is a Neotropical genus of Fabaceae (Caesalpinioideae, mimosoid clade), comprising 36 taxa occurring from Nicaragua to Southern Brazil, most of them found and endemic in Brazil, being especially frequent in savannas (Cerrado) and the Amazon Forest. This synopsis presents the designation of 16 lectotypes, eight new synonyms, a new combination with a nomenclatural status change, a species’ reestablishment, two doubtful names and three excluded species. We also present nine new species, which are described and illustrated. All the species are accompanied by comments on geographical distribution, habitat and IUCN Conservation status.